Mexico: From indigenous education to rural education - Calderón Mólgora, Marco Antonio (Historia y Memoria de la Educación, 2018)
This essay refers to the history of rural education in Mexico in the context of the state configuration that emerges as a result of the social revolution during the decade of 1910. It shows how the perception of the «the indigenous problem» is transformed into «the rural problem» and the way in which such transformation is related to the strategies of the federal government to solve one of the most important «national problems». Since the rural education project faced difficulties and resistances, the Ministry of Public Education tested different methods in order to find strategies to «civilize» and «forging a sense of the fatherland». This work emphasizes some of the strategies undertaken by the Ministry of Public Education to educate the population that lived in the countryside in the 1920s. Although politicians and intellectuals emphasized the urgency of rescuing local needs in the process of building the modern nation, a central element of this process is that rural education sought the industrialization of agricultural production, which implied very significant changes in the everyday life of indigenous and peasant communities a